Analysis Of The Profits Of The Floating Net Cage Business And Its Contribution To Household Income During The Covid 19 Pandemic In Benua Riam Village, Aranio District - Gusti MARLIANI; Diah ISMAYANTI (International Journal of Environmental, Sustainability, and Social Science, 2022)
This study aims to determine: the production costs, revenues, and profits of floating net cages and their contribution to total household income during the covid 19 pandemic in Benua Riam Village, Aranio District in one production in 2020. This type of research uses quantitative research with descriptive analysis. The study started from January to May 2021. The population in the study amounted to 70 households who were active in the floating net cage business, the sampling method used criteria so that a sample of 32 households was obtained. Data analysis techniques used, production cost analysis techniques, revenues, and profits as well as the percentage of the contribution of the floating net cage business to household income. The results showed that: the production costs incurred by respondents in one production during the COVID-19 pandemic in 2020 amounted to Rp. 792,876,391 with an average of Rp. 24,186,876/person, while the revenue is Rp. 933,370,900/one harvest with an average income of Rp. 29,164,840/person, in one harvest. The benefits obtained during the COVID-19 pandemic in 2020 amounted to Rp. 140,472,509/one harvest, with an average profit of Rp. 4,389,765/person. The contribution given by the floating net cage business to the household income of respondents in Benua Riam Village during the Covid-19 Pandemic of 2020 was 37.91%, according to the contribution criteria, this contribution is classified as moderate because it contributes between 30 - 50%.